2008
DOI: 10.1007/s00244-008-9272-9
|View full text |Cite
|
Sign up to set email alerts
|

Carryover of Perfluorooctanoic Acid (PFOA) and Perfluorooctane Sulfonate (PFOS) from Soil to Plants

Abstract: Within the scope of a joint project to study soil-to-plant carryover of polyfluorinated compounds (PFCs), five cultivated plants (spring wheat, oats, potatoes, maize, and perennial ryegrass) were sown or planted in Mitscherlich pots. Six variants per species were used, each with a different concentration level of PFOA and PFOS (from 0.25 to 50 mg/kg as aqueous solution) to detect possible concentration dependence in the transfer of these two PFCs from soil to plant. PFOA and PFOS were detected by liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
184
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 274 publications
(218 citation statements)
references
References 37 publications
18
184
5
1
Order By: Relevance
“…Results obtained by Lechner and Knapp (2011) showed that PFOA concentrations in carrots and potatoes were higher than those of PFOS. However, PFOS concentrations in maize ears were higher than PFOA (Stahl et al 2009). Our finding showed that the steady concentrations of PFOS in maize roots and shoots were higher than those of PFOA ( Fig.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Results obtained by Lechner and Knapp (2011) showed that PFOA concentrations in carrots and potatoes were higher than those of PFOS. However, PFOS concentrations in maize ears were higher than PFOA (Stahl et al 2009). Our finding showed that the steady concentrations of PFOS in maize roots and shoots were higher than those of PFOA ( Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Liu (2009) reported that PFOS was more toxic than PFOA for cucumber, higher concentrations. Stahl et al (2009) suggested that toxic effect of PFOS and PFOA to plants was dependent on plant species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations